AQbD assisted UPLC method development and validation of tirzepatide in bulk and pharmaceutical dosage form - Sunitha Panthagada; M. Sivakumar (Journal of Applied Pharmaceutical Research, 2026)
Background: Tirzepatide is a USFDA-approved (2023) synthetic drug that primarily targets blood sugar metabolism for chronic weight management, obesity-related conditions, and type 2 diabetes. In this study, we aim to develop a reliable, sensitive UPLC method for estimating Tirzepatide using Analytical Quality by Design (AQbD) to optimize chromatographic conditions. Methodology: The finalized method was developed using the Agilent 1290 Infinity II LC System, with a Phenomenex C18 column (50 x 1.7 mm, 2.1 µm), using a mobile phase of acetonitrile and trifluoroacetic acid buffer (37.07:62.93, v/v) at a flow rate of 0.57 mL/min and a Photo Diode Array detector at 264 nm. Result and Discussion: The method validation showed linearity over the range of 12.5–75 µg/mL (R² = 0.9995). The intraday and interday precision (%RSD) values were 0.603 and 0.791, respectively, confirming the method's reproducibility. Limit of Detection and Limit of Quantification values were calculated from S/N ratios of the prepared samples and were 0.6 and 2, respectively. Accuracy was validated to be 99.3-101.1%. The forced degradation studies were conducted under stress conditions, including acid, alkali, peroxide, reduction, photodegradation, and hydrolysis, with tirzepatide showing degradation percentages of 1.3%, 11.3%, 12.1%, 2.1%, 1.7%, and 2.9%. Conclusion: The developed UPLC method for quantifying tirzepatide was found to be significant, with all evaluated parameters in agreement with ICH guidelines. The proposed method is efficient, straightforward, and dependable, rendering it appropriate for routine quality control of tirzepatide in bulk and pharmaceutical formulations